Efficacy and safety of anlotinib in patients with desmoid fibromatosis: a retrospective analysis - Xie, Mengzhang; Huang, Qi; Gong, Taojun; Wang, Yitian; Li, Zhuangzhuang; Lu, Minxun; Luo, Yi; Min, Li; Zhou, Yong; Tu, Chongqi (Frontiers in Oncology, 2024)
Introduction Desmoid fibromatosis is an aggressive fibroblastic neoplasm with a high propensity for local recurrence. Targeted therapy for Desmoid fibromatosis represents a novel avenue in systemic treatment. Anlotinib, a novel multitargeted angiogenesis inhibitor, represents a novel approach for targeted therapy. Therefore, this study aims to assess the efficacy and safety of anlotinib in patients with Desmoid fibromatosis. Methods We retrospectively gathered the clinical medical records of Desmoid fibromatosis patients who underwent anlotinib treatment between June 2019 and November 2023 at our center. Anlotinib was initiated at a daily dose of 12 mg and adjusted based on drug-related toxicity. Tumor response was evaluated using the Response Evaluation Criteria in Solid Tumors 1.1 criteria. Progression-free survival served as the primary endpoint and was analyzed utilizing the Kaplan–Meier method. Results In total, sixty-six consecutive patients were enrolled. No patients achieved a complete response; however, fourteen patients (21.21%) exhibited a partial response, while forty-six patients (70%) experienced disease stability. Progressive disease was observed in 6 patients (9.10%), and the progression-free survival rates at 12 and 36months were 89.71% and 82.81%, respectively. The disease control rate was 90.91%, while the objective response rate was 21.21%. Conclusion Anlotinib proves effective in managing recurrent and symptomatic patients with Desmoid fibromatosis. However, the toxicity profile of anlotinib presents a higher risk of Hand-Foot Skin Reaction and hypertension. Therefore, given that 41.67% of patients were subjected to dose adjustments associated with the initial dose of 12 mg, implementing dosage reductions may help balance efficacy with side effects.